Dimensi Kualitas Pelayanan yang Mempengaruhi Kepuasan Pelanggan Pada Perhotelan di Purwodadi Kabupaten Grobogan - Marsudi, Hidup; Nalurita, Wening (STIE Atma Bhakti, 2024)
This study was conducted to determine the dimensions of service quality, namely physical evidence, reliability, responsiveness, assurance, and care that affect customer satisfaction at the gift hotel Purwodadi and analyze the most dominant factors in influencing customer satisfaction. The processing of data obtained from data collection of questionnaires distributed to 80 respondents. The data analysis technique used a questionnaire which was then measured with a linkert scale. Based on the research, the regression equation was obtained as follows: Y = 5.722+0.025X1+0.039X2+0.313X3+0.455X4+0.272X5+e Based on statistical data analysis, all indicators are valid and the variables are reliable. In the classical assumption test, the regression model is free of multicollinearity and there is no heteroscedasticity and is normally distributed. In order for each individual the most dominant variable is the assurance variable with a regression coefficient of 0.455, then the responsiveness is 0.313, the concern is 0.272, the reliability is 0.039 and the lowest is the physical evidence 0.025. The bounty hotel needs to improve the elements that are still lacking and maintain the things that have been rated well by customers.